Avoidance of MAIT cells is an essential determinant of Listeria monocytogenes pathogenesis - Rafael Rivera-Lugo; Jesse Garcia Castillo; Mariya Lobanovska; Eugene Tang; Andrea Anaya-Sanchez; Scott Espich; Sarah A. Stanley; Michel DuPage; Daniel A. Portnoy (Proceedings of the National Academy of Sciences, 2026)
Mucosal-associated invariant T (MAIT) cells are among the most conserved and abundant innate-like T cells in humans that recognize microbial-derived riboflavin precursors and elicit potent antimicrobial responses. The foodborne pathogen Listeria monocytogenes is a broad host-range facultative intracellular pathogen that lacks the riboflavin biosynthetic pathway, leading us to hypothesize that this deficiency is pathoadaptive and allows the pathogen to evade MAIT cells. Here, we show that L. monocytogenes strains engineered to produce riboflavin ( L. monocytogenes - ribDEAHT ) are attenuated in wild-type mice but fully virulent in MAIT cell–deficient mice. Infection with L. monocytogenes - ribDEAHT prompted rapid and robust MAIT cell expansion in multiple tissues and required the cytolytic effector perforin to eliminate infected cells in vivo and in vitro. We also assessed the therapeutic potential of L. monocytogenes - ribDEAHT- stimulated MAIT cells in both infectious disease and cancer mouse models. Therapeutic administration of L. monocytogenes - ribDEAHT provided protection against Francisella tularensis in the lungs and inhibited tumor growth even in the absence of CD8 + T cells. These findings reveal the importance of MAIT cell evasion during L. monocytogenes infection and highlight the therapeutic potential of engineered L. monocytogenes to activate and harness MAIT cells for protection against infectious disease and cancer.